Electron Spin Resonance Dosimetry Studies of Irradiated Sulfite Salts - Amanda Burg Rech; Angela Kinoshita; Paulo Marcos Donate; Otaciro Rangel Nascimento; Oswaldo Baffa (Molecules, 2022)
The study of new materials for radiation dosimetry is important to improve the present state of the art and to help in cases of accidents for retrospective dosimetry. Sulfites are compounds that contain a sulfur ion, widely used in the food industry. Due to the significant application of these compounds, sulfites are interesting candidates for accidental dosimetry, as fortuitous radiation detectors. The presence of the SO3− anion enables its detection by electron spin resonance (ESR) spectroscopy. The Dose–Response behavior, signal stability and other spectral features were investigated for sodium sulfite, sodium bisulfite, sodium metabisulfite and potassium metabisulfite, all in crystalline forms. The ESR spectrum of salts presented stability and proportional response with dose, presenting potential for dosimetry applications.